Mechanical and dynamical properties of racing snowboards and their modification by different binding plates - Wolfsperger, F.; Rhyner, H. (Procedia Engineering, 2014)
One-piece binding plates in snowboard racing have initially been introduced at the Olympics in 2006 by the later gold medalist. Today different types of such binding plates are used and play an important role to setup the equipment according to individual preferences. This study aims to quantify to what extent different binding plates modify the mechanical and dynamical properties of racing snowboards. The mechanical and dynamical properties of five racing snowboards with and without binding plates were characterized by laboratory measurements of the following parameters: Overall bending stiffness, bending stiffness distribution, torsional stiffness of rear and front body, force distribution along the running base, natural frequencies and their damping ratios. An increase in bending stiffness of 3.5% to 10.7% was measured for the different binding plates. Concerning torsional stiffening, large differences were found between the tested items of 0% to 19.7% for the front body and 2.6% to 35.1% for the rear body of the snowboard-binding plate systems. Free vibration tests showed a strong increase in damping for 4 of 5 binding plates while one plate damped distinctively less, which was also the only binding plate causing a clear change of the force distribution along the running base. While all plates cause relatively low bending stiffening, indicating a consensus about what a binding plate in snowboard racing should provide, the role of torsional stiffening and damping is probably considered controversially among manufactures and athletes as strong differences were found for these properties between the tested binding plates. It could be shown that current binding plates do partly modify the mechanical and dynamical properties of the snowboard - binding plate system to an extent that is larger than the differences between the analyzed racing snowboards itself.